A strictly increasing function f : N → N is such that:
f ( f ( n ) ) = 3 n ∀ n ∈ N
Find f ( 2 0 1 5 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The Induction / Bounding is the best way to approach this problem.
Very very meticulous!
What if we try finding the function f ( x ) which satisfies the given relation. Idk why i am not able to find it. (Though i am getting f ( x ) = 3 x which satisfies the relation but its obviously not possible) Can we do this by my approach or i am just lagging somewhere?
It's easy to construct the values of the function for the initial integer values. Because the function has to be strictly increasing, this makes it routine . It's seen that f ( 3 k ) = 2 × 3 k , for k ≥ 1 and it increases by unity in each step until f ( 2 × 3 k ) = 3 k + 1 .
Similarly, from f ( 2 × 3 k ) , till f ( 3 k + 1 ) , the values increase by multiples of 3, till we get f ( 3 k + 1 ) = 2 × 3 k + 1 .
Thus any value can be computed. 2015 lies between 3 6 and 3 7 ; and we get: f ( 2 0 1 5 ) = 3 8 5 8
Precisely. To be more helpful, we figure out f ( 1 ) by the following logic: f ( 1 ) is not 1 . Why? because then the given equality given does not fit. So, f ( 1 ) = x > 1 . But, f ( x ) = f ( f ( 1 ) ) = 3 , Since, x > 1 , f ( x ) > f ( 1 ) , (increasing function). Thus, 3 > f ( 1 ) . So, now we know: f ( 1 ) = 2 . and so, f ( 2 ) = 3 . This gives f ( 3 ) = 6 and also, f ( 6 ) = 9 . Observe the last two equalities. They tell us that 6 < f ( 4 ) < f ( 5 ) < 9 . Bingo! f ( 4 ) = 7 and f ( 5 ) = 8 . Then move on further like this. Observe the pattern for powers of three and the intermediates and find the answer!
Problem Loading...
Note Loading...
Set Loading...
Aritro Pathak Although your approach is correct I will give a rigorous proof of our conjecture. We need to prove that
For n = 0 , 1 , 2 , . . .
f ( 3 n ) = 2 ⋅ 3 n and f ( 2 ⋅ 3 n ) = 3 n + 1
Proof: We will use induction. Notice that f ( 1 ) = 1 otherwise 3 = f ( f ( 1 ) ) = f ( 1 ) = 1 which is not true. Since f ( k ) is a positive integer for all positive integers k , we conclude that f ( 1 ) > 1 .Since f ( n + 1 ) > f ( n ) , f is increasing. Thus 1 < f ( 1 ) < f ( f ( 1 ) ) = 3 or f ( 1 ) = 2 . Hence f ( 2 ) = f ( f ( 1 ) ) = 3 .
Suppose that for some positive integer n ≥ 1 ,
f ( 3 n ) = 2 ⋅ 3 n and f ( 2 ⋅ 3 n ) = 3 n + 1
f ( 3 n + 1 ) = f ( f ( 2 ⋅ 3 n ) ) = 2 ⋅ 3 n + 1
f ( 2 ⋅ 3 n + 1 ) = f ( f ( 3 n + 1 ) ) = 3 n + 2
as desired. This completes the induction and hence the "guess" is proved.
There are 3 n − 1 integers which we call ′ m ′ such that 3 n < m < 2 ⋅ 3 n and there are 3 n − 1 integers p such that
f ( 3 n ) = 2 ⋅ 3 n < p < 3 n + 1 = f ( 2 ⋅ 3 n )
f is increasing so f ( 3 n + m ) = 2 . 3 n + m for 0 ≤ m ≤ 3 n
Therefore f ( 2 ⋅ 3 n + m ) = f ( f ( 3 n + m ) ) = 3 ( 3 n + m ) for 0 ≤ m ≤ 3 n
Hence f ( 2 0 1 5 ) = f ( 2 ⋅ 3 6 + 5 4 3 ) = 3 ( 3 6 + 5 4 3 ) = 3 8 1 6
I have written it very very cautiously still bring my attention towards mistakes,if any,thank you!!